Gender and live weight on carcass and meat characteristics of donkeys - Hernández Briano, Pedro; Ramírez Lozano, Roque Gonzalo; Carrillo Muro, Octavio; López Carlos, Marco Antonio; Méndez Llorente, Fabiola; Aguilera Soto, Jairo Iván (Universidade Federal de Santa Maria, 2018)
ABSTRACT: One hundred eighty-nine Catalan crossbreed donkeys (Equus africanus asinus) were used to evaluate the effect of gender (gelding, n=106; or female, n=83) and live weight at slaughter (LW) (<100kg, n=25; 101 to 125kg, n=42; 126 to 150kg, n=85; and 151>kg, n=37) on carcass characteristics, non-carcass components and meat and fat color. Geldings had greater (P<0.05) carcass weight, carcass dressing and *L value of subcutaneous fat than females; but females had greater (P<0.05) cooling loss, a* value of semitendinosus muscle and b* value of subcutaneous fat. Donkeys with more than 126kg of LW showed greater (P<0.05) carcass weight and dressing and lower (P<0.05) cooling loss compared to lighter donkeys. The a* value of semitendinosus muscle and abdominal fat was greater in heaviest donkeys (>151kg). Meanwhile, the LW did not affect the color (L*, a* and b* values) of subcutaneous fat (P>0.05). These results suggested that both gender and live weight should be considered when producing meat from donkeys. It is advisable to use geldings weighing more than 126kg at slaughter to obtain the greatest weight and carcass yield. Key words: carcass characteristics, donkey, gender, weight, meat